Los Modernistas - Pérez Petit, Víctor 1871-1947 (Obras completas. Crítica)
Contiene: Henrik Ibsen, Herhart Hauptmann, Gabriel D'Nunzio, León Tolstoi, Paul Verlaine, Eugenio de Castro, Augusto Strindberg, Basilio Yakchakof, Stéphane Mallarmé, Oscar Wilde, Walt Whitman, Friedrich Nietzsche, Enrique Gómez Carrillo, Gustave Kahn, Mauricio Maeterlinck